EANM guideline on the validation of analytical methods for radiopharmaceuticals - Nic Gillings; Sergio Todde; Martin Behe; Clemens Decristoforo; Philip Elsinga; Valentina Ferrari; Olaug Hjelstuen; Petra Kolenc Peitl; Jacek Koziorowski; Peter Laverman; Thomas L. Mindt; Meltem Ocak; et al. (SpringerOpen, 2020)
Abstract Background To fulfil good manufacturing requirements, analytical methods for the analysis of pharmaceuticals for human and vetinary use must be validated. The International Conference on Harmonization of Technical Requirements for Registration of Pharmaceuticals for Human Use (ICH) has published guidance documents on the requirements for such validation activities and these have been adopted by the European Medicines Agency, The U.S. Food and Drug Administration (FDA) and other regulatory bodies. These guidance documents do not, however, fully address all the specific tests required for the analysis of radiopharmaceuticals. This guideline attempts to rectify this shortcoming, by recommending approaches to validate such methods. Results Recommedations for the validation of analytical methods which are specific for radiopharmaceutials are presented in this guideline, along with two practical examples. Conclusions In order to comply with good manufacturing practice, analytical methods for radiopharmaceuticals for human use should be validated.